(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
The paper about Islamic civilization: a construct of the transformation of science aims to address the problem of the construct of the transformation of science in Islam. Through the approach of Islamic civilization in this paper, the problem can be answered. This paper concludes with the conclusion that social and religious change finds relevance when human history is factually never separated from the side of its religious life.